Identification of Evolutionarily Conserved Exons as Regulated Targets for the Splicing Activator Tra2β in Development - Sushma Nagaraja Grellscheid; Caroline Dalgliesh; Markus Storbeck; Andrew Best; Yilei Liu; Miriam Jakubik; Ylva Mende; Ingrid Ehrmann; Tomaž Curk; Kristina Roßbach; Cyril F. Bourgeois; James Stévenin; et al. (2011)
Alternative splicing amplifies the information content of the genome, creating multiple mRNA isoforms from single genes. The evolutionarily conserved splicing activator Tra2β (Sfrs10) is essential for mouse embryogenesis and implicated in spermatogenesis. Here we find that Tra2β is up-regulated as the mitotic stem cell containing population of male germ cells differentiate into meiotic and post-meiotic cells. Using CLIP coupled to deep sequencing, we found that Tra2β binds a high frequency of exons and identified specific G/A rich motifs as frequent targets. Significantly, for the first time we have analysed the splicing effect of Sfrs10 depletion in vivo by generating a conditional neuronal-specific Sfrs10 knock-out mouse (Sfrs10fl/fl; Nestin-Cretg/+). This mouse has defects in brain development and allowed correlation of genuine physiologically Tra2β regulated exons. These belonged to a novel class which were longer than average size and importantly needed multiple cooperative Tra2β binding sites for efficient splicing activation, thus explaining the observed splicing defects in the knockout mice. Regulated exons included a cassette exon which produces a meiotic isoform of the Nasp histone chaperone that helps monitor DNA double-strand breaks. We also found a previously uncharacterised poison exon identifying a new pathway of feedback control between vertebrate Tra2 proteins. Both Nasp-T and the Tra2a poison exon are evolutionarily conserved, suggesting they might control fundamental developmental processes. Tra2β protein isoforms lacking the RRM were able to activate specific target exons indicating an additional functional role as a splicing co-activator. Significantly the N-terminal RS1 domain conserved between flies and humans was essential for the splicing activator function of Tra2β. Versions of Tra2β lacking this N-terminal RS1 domain potently repressed the same target exons activated by full-length Tra2β protein.